Generation of Novel Human Red Blood Cell-Bearing Humanized Mouse Models Based on C3-Deficient NOG Mice - Yamaguchi, Takuya; Katano, Ikumi; Otsuka, Iyo; Ito, Ryoji; Mochizuki, Misa; Goto, Motohito; Takahashi, Takeshi (Frontiers in Immunology, 2021)
Despite recent advances in immunodeficient mouse models bearing human red blood cells (hRBCs), the elimination of circulating hRBCs by residual innate immune systems remains a significant challenge. In this study, we evaluated the role of mouse complement C3 in the elimination of circulating hRBCs by developing a novel NOG substrain harboring a truncated version of the murine C3 gene (NOG-C3ΔMG2-3). Genetic C3 deletion prolonged the survival of transfused hRBCs in the circulation. Chemical depletion and functional impairment of mouse macrophages, using clodronate liposomes (Clo-lip) or gadolinium chloride (GdCl3), respectively, further extended the survival of hRBCs in NOG-C3ΔMG2-3 mice. Low GdCl3 toxicity allowed the establishment of hRBC-bearing mice, in which hRBCs survived for more than 4 weeks with transfusion once a week. In addition, erythropoiesis of human hematopoietic stem cells (hHSCs) was possible in NOG-C3ΔMG2-3/human GM-CSF-IL-3 transgenic mice with Clo-lip treatment. These findings indicate that mouse models harboring hRBCs can be achieved using NOG-C3ΔMG2-3 mice, which could facilitate studies of human diseases associated with RBCs.